Littérature et migration : imaginaire littéraire national, créolisation, cybermigration - Sophie Coavoux (Cahiers Balkaniques)
While the links between literature and migration go back a long way, notably in the Greek case, they have been opening up new horizons since the 1990s. The reconfiguration of migratory experiences, the global context of transnational mobility, the renewal of migrant writing in a globalised world, as well as the cybermigration of literature in the age of the Internet no longer fit the idea of a national literature, for a long time in line with the idea of the nation as an “imagined community” (Anderson). These new forms of writing on the move, produced by the “creolisation” of national identities (Glissant), require both a decentred perspective and a critical turn. The aim of this article is to provide, in an exploratory way, an overview of these issues, both in literature and literary studies, and to address some of the historiographical and epistemological problems they raise.